The effect of exercise on cerebral blood flow and executive function among young adults: a double-blinded randomized controlled trial - Jianxiu Liu; Leizi Min; Ruidong Liu; Xiaoyu Zhang; Meiting Wu; Qian Di; Xindong Ma (Scientific Reports, 2023)
Abstract Studies have demonstrated that exercise benefits executive function. However, it remains unclear which type of exercise is optimal for preserving executive function among young adults and the cerebral blood flow (CBF) mechanisms that underlie exercise-induced cognitive benefits. Therefore, this study aims to compare the intervention effects of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on executive function and the CBF mechanism. This was a double-blinded, randomized, controlled trial study conducted between October 2020 and January 2021 (ClinicalTrials.gov identifier: NCT04830059). Ninety-three healthy young adults (25.23 ± 2.18 years old; 49.82% male) were randomized into the HIIT (N = 33), MICT (N = 32), and control (N = 28) groups. Participants in exercise groups were guided to perform 40 min of HIIT and MICT three times a week for 12 weeks, while the control group received health education for the same period. The primary outcomes, changes in executive function assessed by the trail-making test (TMT), and CBF measured by transcranial Doppler flow analyzer (EMS-9WA), were evaluated before and after the interventions. The time taken to complete the TMT task improved significantly in the MICT group compared to the control group [β = −10.175, 95%, confidence interval (CI) =  −20.320, −0.031]. Additionally, the MICT group showed significant improvements in the pulsatility index (PI) (β = 0.120, 95% CI = 0.018, 0.222), resistance index (RI) (β = 0.043, 95% CI = 0.005, 0.082), and peak-systolic/end-diastolic velocity (S/D) (β = 0.277, 95% CI = 0.048, 0.507) of CBF compared to the control group. The time taken to complete the TMT was associated with the velocity of peak-systolic (F = 5.414, P = 0.022), PI (F = 4.973, P = 0.012), and RI (F = 5.845, P = 0.006). Furthermore, the accuracy of TMT was associated with PI (F = 4.797, P = 0.036), RI (F = 5.394, P = 0.024), and S/D (F = 4.312, P = 0.05) of CBF. A 12-week MICT intervention improved CBF and executive function more effectively than HIIT among young adults. Furthermore, the findings suggest that CBF was one of the potential mechanisms underlying the cognitive benefits of exercise in young people. These results provide practical evidence supporting the promotion of regular exercise to maintain executive function and improve brain health.